The Geriatrics Workforce Enhancement Program: Occupational Therapy 's Imperative Role in Interprofessional Education - Jeanine Nonaillada; Natalie C. Gangai; Chrysanne Eichner; Rosario Costas-Muniz (Scholarworks @ WMU, 2017)
This paper will expound on the findings discovered from efforts made by including an occupational therapist on an interprofessional education initiative charged with developing content to enhance knowledge of geriatrics for health care providers, community-dwelling older adults, and caregivers in medically underserved areas. We will describe the actions of the interprofessional team and present data about the impact of collaborative, systematic input on one educational program taught primarily by the occupational therapist. We will then describe the personal and professional growth opportunities experienced by the occupational therapist on this initiative, and impart the challenges faced and provide recommendations to overcome them. Finally, we will discuss practical implications for advancing interprofessional education and occupational therapy at other institutions